In silico studies predict role of PgUCP1 from Pennisetum glaucum in heat stress tolerance - MAIBAM, ALBERT; VISHWAKARMA, HARINDER; PADARIA, JASDEEP CHATRATH (The Indian Journal of Agricultural Sciences, 2019)
Heat stress adversely affects crop plants leading to high yield losses. To protect themselves, plants respond by expressing large number of genes. This includes reported/known genes as well as hypothetical or uncharacterized genes. Genes for uncharacterized or hypothetical proteins form a major proportion of data generated by different functional genomic approaches. It is quite important to assign function to these stress responsive uncharacterized genes for better understanding of stress responsive molecular mechanisms. In the present study, full length coding sequence of a gene for an uncharacterized protein1 PgUCP1 (624 bp) was cloned from pearl millet genotype 841-B (ICMB841) at National Institute for Plant Biotechnology, New Delhi in year 2017–18. The gene PgUCP1(Accession number MK33595) was identified in the heat responsive transcriptome data generated in leaf tissue of P. glaucum plants grown in National Phytotron Facility,IARI, New Delhi. The CDS was successfully isolated and cloned in pGEM-T easy vector. The predicted 3-Dimensional structure of PgUCP1 showed that it is able to interact with ligands [AMP (Adenosine monophosphate), ADP (Adenosine diphosphate), ATP (Adenosine triphosphate)] depicting presence of active site residues. Phylogenetic analysis showed PgUCP1 to be closely related to zinc finger protein of Setaria italica. The predicted transcript in this study clearly indicated its role in providing heat stress tolerance. Further, the role of identified transcript can be validated in model plant system under abiotic stress conditions. The gene may be a potent prospective resource for development of abiotic stress tolerant crops.